Searching for Frataxin Function: Exploring the Analogy with Nqo15, the Frataxin-like Protein of Respiratory Complex I from Thermus thermophilus - Doni, Davide (2024)
Nqo15 is a subunit of respiratory complex I of the bacterium Thermus thermophilus, withstrong structural similarity to human frataxin (FXN), a protein involved in the mitochondrial diseaseFriedreich’s ataxia (FRDA). Recently, we showed that the expression of recombinant Nqo15 canameliorate the respiratory phenotype of FRDA patients’ cells, and this prompted us to furthercharacterize both the Nqo15 solution’s behavior and its potential functional overlap with FXN, usinga combination of in silico and in vitro techniques. We studied the analogy of Nqo15 and FXN byperforming extensive database searches based on sequence and structure. Nqo15’s folding andflexibility were investigated by combining nuclear magnetic resonance (NMR), circular dichroism,and coarse-grained molecular dynamics simulations. Nqo15’s iron-binding properties were studiedusing NMR, fluorescence, and specific assays and its desulfurase activation by biochemical assays. Wefound that the recombinant Nqo15 isolated from complex I is monomeric, stable, folded in solution,and highly dynamic. Nqo15 does not share the iron-binding properties of FXN or its desulfuraseactivation function.